2003
DOI: 10.1213/01.ane.0000048977.66133.d5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Epidural Infusion of Large Concentration/Small Volume Versus Small Concentration/Large Volume of Levobupivacaine for Postoperative Analgesia

Abstract: We demonstrated that a large concentration/small volume of levobupivacaine given as a continuous thoracic epidural infusion provided an equal quality of postoperative analgesia as a small-concentration/large-volume infusion and induced less motor blockade and fewer hemodynamic repercussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 21 publications
5
43
1
2
Order By: Relevance
“…23 Several studies have subsequently demonstrated identical sensory and motor blockade when using local anesthetic solutions of widely different concentrations but of equal drug dose. [2][3][4][5][6][7][8][9][10][11][12]24,25 Some studies even demonstrated improved postoperative analgesia with concentrated epidural local anesthetic infusions 9 and more profound motor block 3,4 and hypotension 3,4 when using dilute solutions. Conversely, other studies have been published that support the superiority of dilute epidural local anesthetics for diffuse low intensity analgesia, particularly in labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…23 Several studies have subsequently demonstrated identical sensory and motor blockade when using local anesthetic solutions of widely different concentrations but of equal drug dose. [2][3][4][5][6][7][8][9][10][11][12]24,25 Some studies even demonstrated improved postoperative analgesia with concentrated epidural local anesthetic infusions 9 and more profound motor block 3,4 and hypotension 3,4 when using dilute solutions. Conversely, other studies have been published that support the superiority of dilute epidural local anesthetics for diffuse low intensity analgesia, particularly in labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17] Indeed, some studies reported an increased intensity of motor block, 7,8 increased hypotension, 7,8 and reduced analgesic effectiveness 16 when using dilute epidural local anesthetics as compared with concentrated drug regimes of equal dose. Dernedde and colleagues [7][8][9] reported an increased intensity of motor block and hypotension when using continuous infusions of bupivacaine administered in a low concentration, high volume (0.15%, 10 mL/h) compared with a high concentration, low volume (0.5%, 3 mL/h) solution. Murdoch et al 14 observed that 0.25% levobupivacaine as a continuous epidural infusion provided better postoperative analgesia without any significant increase in motor blockade compared with a 0.125% levobupivacaine infusion at twice the infusion rate.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Clinical studies of postoperative epidural analgesia provide conflicting evidence about the most important factor in determining the extent of a differential sensory block: absolute dose or volume of epidural local anesthetic. [6][7][8][9][10][11][12][13][14][15][16][17][18] A similar debate has recently re-emerged with labor analgesia. [16][17][18] In this prospective, randomized study in nulliparous women, patient-controlled epidural analgesia (PCEA) was used to administer epidural bupivacaine either as a concentrated (0.25%) or as a dilute (0.0625%) solution and analgesic requirement, maternal satisfaction, motor block and obstetric outcome were compared.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the rate of epidural infusion (in the present case, 10 ml/h), comparative studies between two options -small volumes at high concentrations or large volumes at low concentrations -there is not much difference since the quality of analgesia depends on the total dose administered [16]. However, when post-operative perfusion continues for more than 72 hours we should pause to think whether such a rate is suitable given the high frequency of catheter migration described in.…”
Section: Discussionmentioning
confidence: 85%